Health Education Pemenuhan Gizi Pada Anak Stunting Di Desa Kampung Delima - Lubis, Hiqmah Purnama; Hilintri, Yatri; Sari , Lara Harnelis; Nopitabela , Vreciosa; Arishandi , Ninda Putri; Sutarni, Sutarni; Setiawan , Arief; Rohani , Tuti; Azissah , Danur (Jurnal Kewirausahaan dan Bisnis, 2025)
Stunting is a chronic nutritional problem in toddlers which is characterized by shorter height compared to children their age. The incidence of short toddlers or commonly known as stunting is one of the nutritional problems experienced by toddlers in the world today. There are 78,572 target families at risk of stunting in Bengkulu Province based on 2023 data. This number has decreased compared to 2022 of 97,327 target families at risk of stunting. In general, stunting cases in Bengkulu are at 20.2 percent. The cause that often occurs in society is the mother's lack of knowledge regarding the nutritional needs of children during the growth period. Stunting in children is caused by nutritional intake of toddlers, the presence of infectious diseases, maternal factors with poor nutrition during preconception, pregnancy and lactation, genetic factors, exclusive breastfeeding, food availability, socio-economic factors, maternal education level, maternal nutritional knowledge and environmental factors. One effort to improve the behavior of mothers of toddlers is through health education. There are 3 cases of stunted children in Kampung Delima Village, for this reason we carry out community service regarding stunting. A total of 3 families with stunted children who were given counseling were able to understand and comprehend the material presented by the presenters regarding meeting children's nutritional needs. As a result of this activity, knowledge about fulfilling nutrition in children has increased after the outreach activities were carried out.